DATA SYNCHRONIZATION MODEL FOR HETEROGENEOUS MOBILE DEVICE DATABASES AND SERVER-SIDE DATABASE - IMAM, ABDULLAHI ABUBAKAR (2015)
Database synchronizationcan be definedas a process of establishing data equivalence among two or more data collections. Looking at how rapid mobile devices have evolved in terms ofvariations and sophistication, it is important to seek a solution that can utilize their individual capacities such as CPU, memory, bandwidth and processing power when performing similar tasks. In so doing, many research works have opted for development of solutions which are tailored to a particular vendor or vendor specific. For database synchronization, similar approach can 'be observed. This approacheven though effective, requiresextra step to be done by the server since each device type of different vendors will require special synchronization treatment. Hence, hi this study, a model which is caied Heterogeneous Mobile Database Synchronization Model (HMDSM) is proposed for enabling data synchronization between the heterogeneous mobile devices' and server-side's databases, such that the mobile devices (regardless of their individual differences) can synchronize their data with the server-side database.